Pengaruh Variasi Arah dan Massa Serat TKKS terhadap Kekuatan Material Komposit Termoset - Rendy Rendy; Syahrizal Syahrizal (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2022)
Abstract Oil palm empty bunches (TKKS) are industrial solid waste, oil palm empty bunches which are currently only thrown away or burned, causing environmental pollution. One of the efforts to overcome this problem is to use it for the manufacture of new materials. In this study, the variations in the direction of the fibers used were 0 °, 30 °, 45 ° 60 ° and 90 ° with variations in the mass of the fibers used in this study, namely 5%, 10% and 15% of the Empty Oil Palm Fruit Bunch. From the results of data processing on OPEFB fiber composite material, the highest impact price (HI) was found in the 0 ° direction specimens with a percentage of 15% OPEFB fibers of 0.330 J / mm2 and the smallest impact price (HI) was found in 90 ° direction specimens with a percentage of 5% OPEFB fibers. amountiith the Getas fault form.